Analysis Production Dodol Manggis Leuser Mountain as Food to Eat, To Revenue District Community Kutacane Southeast Aceh - Nasruddin, Nasruddin; Soefi, Roezaini (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Mangosteen is one of the types of fruits that thrives at the foot of Mount Leuser Kutacane, Southeast Aceh district, Mangosteen is one of the fruits that contain a lot of anti-oxidant, anti-bacterial, anti-inflammatory and anti-carcinogenic substances, anti-proliferation and contains a variety of Vitamin C, Vitamin B2, Folate, Magnesium and Xonthoes. All of these are very beneficial for the human body. Mangosteen fruit is exported out of town and even abroad with mangosteen fruit sorting. The rest of the soteran becomes a problem for the community so that it becomes a discarded item. With this research, it is hoped that this mangosteen waste product (soteran) can be appointed as a product, so that this product can become one of the culinary foods of Kutacane, Southeast Aceh Regency. The resulting product is a food product, namely Dodol Mangosteen. The purpose of this study is to introduce this mangosteen lunkhead so that it can be accepted by the wider community. And to know the process of making dodol from mangosteen flesh, knowing the formulation of adding glutinous rice flour with the addition of brown sugar in making dodol. And the parameters observed were chemical analysis (water and fat content), and this research was carried out by organoleptic tests. This organoleptic test is a hedonic method of panelists' preference for texture, aroma, taste and color. The data obtained were processed using a completely randomized design with three replicates of variables.